PERTUMBUHAN DAN HASIL DUA VARIETAS KACANG TANAH DALAM TUMPANGSARI REPLACEMENT SERIES DENGAN PADI BERAS HITAM SISTEM IRIGASI AEROBIK PADA BEDENG - Siti Zainab; Wayan Wangiyana (Universitas Pendidikan Mataram, 2021)
This study aimed to determine growth and yield of two varieties of peanut in a 2:2 replacement series intercropping system with black rice under aerobic irrigation system on raised-beds. The experiment, carried out on irrigated rice fields in South Kediri village (West Lombok, NTB) from May to August 2019, was arranged according to Split Split-Plot Design with three treatment factors, namely intercropping system as the main plots (T1: intercropping 2:2 rows between peanuts and black rice; T2: peanut monocrop), peanut varieties as the sub-plots (V1: Bison; V2: Hypoma-1 variety), and combinations of inorganic-organic-bio-fertilizers for black rice as the sub-sub-plots (P1: NPK fertilizer only; P2: NPK+Petroganik; P3: NPK+Petroganik+mycorrhiza bio-fertilizer). The intercropped peanut was fertilized only with 200 kg/ha Phonska (NPK). The results indicated that the most influencing treatment factors were intercropping systems and combinations of inorganic-organic-bio-fertilizers. However, there were significant two-factor-interactions, namely between varieties and intercropping systems on peanut leaf number, dry stover weight and dry filled-pod weight, and between intercropping systems and fertilizer combinations on seed yield and harvest index. Dry seed yields were not significantly different between varieties, but were higher under P3 (21.17 g/clump) or P2 (20.67 g/clump) compared to P1 (19.35 g/clump), while peanut intercropped with black rice resulted in higher seed yield (22.10 g/clump) than monocroped peanuts (18.69 g/clump). Based on the interaction between intercropping systems and fertilizer combinations, the highest seed yield was obtained in peanuts intercropped with black rice fertilized with NPK+organic+bio-fertilizer (23.65 g/clump) and the lowest average was in monocropped peanuts (17.87 g/clump).